The Concept of Al-Jumhuriyah Wa Al-Ahkam in Political Philosophy of Ibn Rushd - Fuad Mahbub Siraj; Mohd Roslan Mohd Nor (Religia, 2020)
In political conversation, Ibn Rushd named his political philosophy with the terms â€œAl-Jumhuriyah wa al-Ahkamâ€ (Republic and Law). This political thought is a form of integration of science and deed. In this political context, Ibn Rushd prioritizes freedom and independence. In the perspective of Ibn Rushd, independence is not without rules, but independence and freedom that compatible with religion. In the perspective of Ibn Rushd, such freedom and independence is mirror of democracy. In politics, Ibn Rushdâ€™s thinking is similar to the thoughts of previous philosophers who reconcile between religion and philosophy. According to Ibn Rushd, there is no contradiction between reason and religion, and therefore it is important for reason and religion to work together to uphold the principles of democracy in a country.